The Constitutional Right To Protect Honor, Dignity And Business Reputation Of Police Officers And Its Civil Implementation - Vyacheslav Vladimirovich, Barbin (2019)
The article is devoted to the research on the constitutional right to protect honor and dignity, the mechanism for its implementation in accordance with the norms of civil law. The work reveals the peculiarities of honor, dignity, and reputation of police officers. The interconnection of these categories is due to the dual nature of the status of a policeman as an individual and a representative of the authorities, a determination of his personal and professional qualities. At the same time, on the basis of a communicative approach, a distinction of these categories is proposed.Reputation manifests itself in public relations when a police officer carries out his official duties. In this sphere, the possibilities to protect reputation are limited by the need to ensure freedom of speech, the constitutional right to apply to public authorities. Freedom of speech in these cases has priority, provided its fair use. The protection of the reputation of a police officer is also a means of protecting the reputation of law enforcement agencies and the state as a whole.Honor and dignity as personal non-property rights can be affected in private relationships in which the policeman participates as a private person. At the same time, in the area of private relations, which have a special one-to-one trust-building character, the possibilities to protect honor and dignity are limited.